Understanding SIBO: A Comprehensive Review of Causes, Symptoms, Diagnosis and Treatment Strategies Of Small Intestinal Bacterial Overgrowth - Wilk, Klaudia; Witkowska, Edyta; Ciechański, Marcin; Cholewiński, Szymon; Wilk, Bernadetta; Stachura, Piotr; Rejman, Piotr; Pszczoła, Katarzyna; Jurkiewicz, Katarzyna; Kasprzyk, Aleksandra (Journal of Education, Health and Sport, 2025)
Introduction Small intestinal bacterial overgrowth is defined as a pathological condition characterized by excessive proliferation of colonic-type bacteria within the small intestine (>10⁵ CFU/mL), accompanied by disturbances in the equilibrium of the small intestinal microbiota. Currently, SIBO is an increasingly prevalent clinical condition, affecting a growing number of patients. The objective of this study is to provide a comprehensive analysis of current research and clinical observations to enhance both diagnostic accuracy and therapeutic strategies for this condition. These advancements are crucial for improving treatment outcomes in patients and broadening the overall understanding of gastrointestinal health. Materials and Methods This article presents a comprehensive review of literature derived from the PubMed database, encompassing studies published between 2019 and 2025. Results Patients with SIBO typically present with nonspecific gastrointestinal symptoms which complicate the selection of candidates for further diagnostic evaluation. SIBO frequently coexists with other disorders, leading to an underestimation of its actual prevalence. Accurate diagnosis requires a comprehensive assessment, including physical examination and laboratory tests, as well as specialized diagnostic procedures, such as breath tests or small bowel aspiration and culture. Additionally, differential diagnosis is essential to exclude other conditions with similar clinical presentations. The primary treatment strategy involves antibiotic therapy, combined with a low FODMAP diet, aims to alleviate clinical symptoms and improve patients’ quality of life by eliminating bacterial overgrowth in the small intestine. Conclusions In conclusion, although SIBO is a relatively well-characterized medical condition, further clinical research is still necessary to refine diagnostic methodologies, standardize recognition criteria, and establish specific therapeutic guidelines.